Penerapan Kegiatan Pembelajaran Eksplorasi Dalam Mengembangkan Kognitif Pada Anak Usia Dini Studi Kasus Di TK Yudi Pratama Desa Pagur Satio - Nikmatul Hasanah; Mira Yanti Lubis; Silfa Hafizah Pulungan (Institut Nalanda, 2024)
Education is an important factor in advancing a nation. Through good education, new things are obtained that can be used to create quality human resources. This research aims to: (1) find out how children's cognitive development in recognizing colors at the Yudi Pratama Kindergarten in Pagur Satio Village before implementing exploratory learning activities. (2) To find out how children's cognitive development in recognizing colors at the Yudi Pratama Kindergarten in Pagur Satio Village after implementing exploratory learning activities. The type of research used is classroom action research (PTK) which consists of 2 cycles, each cycle containing planning, implementation, observation and reflection. The subjects of this research were children at Yudi Pratama Kindergarten with a total of 20 children (5 boys and 15 girls). Based on the results of research carried out by researchers, it can be concluded that implementing exploratory learning activities can improve children's cognitive development in recognizing colors at Yudi Pratama Kindergarten, Pagur Satio Village.